Co-producing madness: international perspectives on the public histories of mental illness. Issue 1 (2nd January 2022) - Ellis, Rob; Coleborne, Catharine
Abstract: Public engagement is increasingly seen as an expected part of the armoury of the twenty-first century academic. With increased scrutiny on the humanities, stemming from a neo-liberal critique of their value, it appears to offer a relatively straightforward opportunity to demonstrate the real-world application of research beyond the ivory towers of academia. For historians of madness and mental ill health, the links between their findings and the issues faced by service-users in the here and now are clear. This article, however, offers a critical reflection of both the challenges and opportunities of partnership working. Starting with examples of the longer-term willingness of academics to engage with a wider public, co-produced initiatives from Australia, New Zealand and the United Kingdom are used to examine the changing shape of academic study and how that aligns with trends in public history, museum development and public policy. The article suggests a series of methodological and theoretical interventions in light of decades of service-user and lived experience engagement with historical research and writing. It provides an overview of the often hidden and overlooked challenges of partnership working, including the place of patient and service user 'voice', and touches on the ethical implications of doing so. Rather than seeing potential partners as 'end users of research', we highlight the learning opportunities that arise from new ways of working, as well as emphasising the significant contribution that historical knowledge and expertise can bring to co-produced outputs.